A concepção de religiosidade no pensamento junguiano: questões e perspectivas - Martins, Caio Vinicius (2014)
Already in his time Jung pointed at the lack of openness by science and the spirit of that period for contemplating religiosity in their reflections and, consequently, considering it in their practices. Thus, the Swiss psychiatrist indicated a dichotomy in the modern man‟s psyche that was being developed within a conflictual dynamics, where scientific, materialistic and critical thought overlapped religion and, consequently, the natural religious function of psyche. It was thereby evidenced a clash between science and religion, the first having been dominated and subjected to the second in preceding centuries, but now having imposed its domain and rejected recognition to the second with the same tenacity. Recent research has also identified this same conflict that affects patients and therapists; however, overcoming it is an even more difficult task than one could imagine or wish. This intersection between psychology and religion proves to be an extremely sensitive area. Those are knowledges and practices quite distinct, that require extreme caution and respect from the practitioner. Emergent scientific streams of thought have shown this acknowledgement to religious dimension while welcoming the equivalent disciplinary field without seeking to reduce it to a scientific theory. We believe that the psychology of Carl Gustav Jung has much to contribute in the construction of a channel for dialogue and understanding between the two fields. Between God and reason we will find the human soul, once abandoned by scientists and religious men, having finally found a voice in the Swiss psychiatrist. Moreover, some consider Jung's psychology as a religious psychology, considering his psychotherapy as an essentially religious attitude. With this understanding, we identify a bridge between these two thinking models, namely, science and religion, which in another time would be seen as irreconcilable. Jung‟s thinking, his view of religion and the sacred, his comprehension of modern man‟s disenchantment as well as his therapeutic method provide us with a substantial contribution to dealing with this conflict. The study indicates a need for openness to approach religiosity in therapeutic setting, which is not usually easy or simple due to its sensitive interdisciplinary field. It also points at a new time, a post-secular time, which demands a new religious paradigm that suits the critical spirit of modern man, where Analytical Psychology has much to offer, addressing and attending to the human soul, a channel between psychology and religion, a working path for the psychotherapist